Strategic Management Analysis at McDonald's Fast Food Restaurant, Perdatam Pasar Minggu - Nugraha, Rizki Nurul; Ramli, Muhammad (West Science Interdisciplinary Studies, 2024)
McDonald's, as one of the franchise companies that has a global reputation and is known almost all over the world, operates its business in the fast food sector. The object of this study is McDonald's located in Perdatam, Pasar Minggu. This research method is qualitative, with a qualitative descriptive analysis approach and SWOC analysis. Data collection was carried out by direct observation and interviews with the relevant resource persons in this study. The results showed that, McDonald's features a food menu that is famous for being delicious and diverse, including packaged menu choices, McDonald's consistently displays food product innovations to attract the attention of its consumers. McDonald's success lies not only in its taste excellence, but also in its ability to constantly adapt to changing consumer trends and tastes. The company continues to carry out various management strategies including vigorous promotions involving various media such as social media, television, radio, newspapers, and banners and McDonald's marketing strategies are designed very practically to stay ahead of its peers in the highly competitive fast food industry. The company's internal factors, especially its strengths, are always able to outperform its weaknesses. McDonald's managed to maintain its position in the market by presenting a combination of menu diversity, quality, and product innovation that became the main attraction for customers. Its ability to continuously compete and remain relevant in the market keeps McDonald's as a leader in the fast food industry, maintaining its edge amid fierce competition and ever-changing business dynamics.